Educação em saúde com prostitutas na prevenção das DST/Aids : reflexões à luz de Paulo Freire - Moura, Ana Débora Assis (2007)
Sexually Transmitted Diseases (STD) are considered an occupational risk for prostitutes, and they can be prevented with the use of condom. A conscientization about its importance through health education is necessary, as it is the most efficient strategy in STD/Aids prevention, what will bring changes in behavior, values and attitudes. In face of all this problematic situation of prostitution and its relation with STD, we got interested in understanding the work carried out by the prostitutes from the Association of Prostitutes from Ceará - APROCE concerning STD/Aids prevention. In this context, this study objectified to analyze the educational work carried out by the prostitutes from APROCE concerning STD and Aids prevention, and to verify if this Health Education estimulates reflexion, criticism and behavior change, or if it is only an information provider. This way, we awakened to the relation between the object of study and the theoretical approach based on Paulo Freire’s reflexions, considering that “change”, together with “conscientization”, is a “theme generator” of Paulo Freire’s theoretical practice. It is a qualitative research inspired in Paulo Freire’s theory and practice, and analyzed according to the Critical Theory. The data were grouped according to the stages they were collected: Observing Social Educators and Dialoguing with Social Educators. Later, the second part was divided in two categories: the profile and the dialogue with social educators. In the dialogue with social educators their feelings about the work done were identified, as well as the main difficulties; the facilitator points; how they perceive their results; and the most and least important points of their work. Therefore, we can conclude that being aware of the importance of STD and Aids prevention and changing behavior are not easy tasks because many factors interfere in prostitutes’ lives. The Health Education strategies used by the Association are not estimulating reflexion, criticism and behavior change as expected, but it has given a great step, as they provide information and condom to prostitutes. And, as it is an action that has happened for some years, many women have already changed behavior. More efficient strategies and projects must be carried out so that conscientization and change happen in a shorter period of time. For the obtention of this aim, Health Education methodological strategies in STD/Aids prevention for prostitutes were elaborated